The evaluation of fired clay brick production in terms of energy efficiency: a case study in Turkey - Yuksek, Izzet; Oztas, Saniye Karaman; Tahtali, Gurhan (Springer, 2020)
High energy consumption in building material production has a significant effect on global warming and other environmental pollution, which has brought into prominence building materials whose production consumes less energy and uses renewable energy sources. In particular, the production phase of brick, a commonly used material in building construction, has an important effect on energy consumption. This study aims to obtain and analyse local energy data in each phase of brick production, compare the energy consumption of local brick factories using different kiln types in Turkey, and contribute to the development of processes for energy-efficient brick production. For this purpose, all the necessary energy data were collected from two factories, one of which uses a Hoffman and the other a tunnel kiln in the system boundary from cradle-to-gate. The local energy data were analysed for the two factories on the assumption that they would reflect the data for the same or similar brick production methods and technologies in Turkey, and this local data and data gathered from the literature were compared in terms of energy consumption. The findings point out that while most energy is consumed during the firing process in both factories, the tunnel factory consumes more energy in total than the Hoffman factory because of the clay preparation process and the calorific value and moisture content of the coal used for firing. The study also reveals that the potential exists for energy efficiency gains in brick production in Turkey.
Keywords: Fired brick; Energy; Tunnel kiln; Hoffman kiln